Global burden of ischemic heart disease due to omega-3 deficiency: 204-country analysis, 1990–2021 - Chen, Xiaozhi; Chen, Lei; Yang, Xinyue; Zhang, Zhiqiang (Frontiers in Nutrition, 2025)
AimThis study evaluates the global burden, trends, and dietary risk factors of ischemic heart disease (IHD) from 1990 to 2021, focusing on socioeconomic and demographic variations.MethodsThe study analyzed IHD-related disability-adjusted life years (DALYs), age-standardized rates (ASR), age-standardized mortality rates (ASMR), and fatality counts. Temporal trends were assessed using estimated annual percentage changes (EAPCs). Dietary risk factors, such as seafood omega-3 fatty acid deficiency, were evaluated in relation to the socio-demographic index (SDI).ResultsFrom 1990 to 2021, DALY rates and fatalities from IHD increased globally. Omega-3 fatty acid deficiencies were identified as a significant contributor. ASMR and age-standardized death rates (ASDR) rose most notably in Central Asia and Eastern Europe. Countries with lower SDI levels faced a higher IHD burden. National trends varied, with adverse correlations between IHD burden and SDI primarily linked to dietary risks.ConclusionDeficiencies in omega-3 fatty acids and other dietary risks are key factors driving global IHD patterns. Public health strategies to improve diet, particularly in low- and middle-SDI regions, are essential to reducing the IHD burden.